Impacts of urbanisation on trust: Evidence from an experiment in the field - Elvis Cheng Xu (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2019)
We conduct a field trust game under a natural experiment context to test the impacts of urbanisation on trust. We conjecture that urbanisation, defined in this context as the process of state-led rural-urban migration, contributes to a transformation of trust levels among co-villagers and towards outsiders. We test this conjecture in an experimental approach and more generally, examine whether the urbanisation will produce significant impacts on in-group trust and out-group trust. The research finds that urbanisation does not decrease significantly the trust towards co-villagers, meaning the in-group trust did not change statistically significantly. However, the trust towards outsiders does increase as a result of the state-led urbanisation. We also run a regression on the trust exhibited towards participants in the experiment and found the partial effect of whether they are co-villagers or outsiders weakens as a result of the urbanisation, and therefore conclude urbanisation decreases out-group discrimination in trust.
Keywords: A13; C93; O15; O18; R23; 330; Urbanisation; Trust; Field Experiment